Quantifying the differences in birth outcomes and out-of-pocket costs between Australian Defence Force servicewomen and civilian women: A data linkage study. Issue 5 (September 2022) - Bull, Claudia; Ellwood, David; Toohill, Jocelyn; Rigney, Azure; Callander, Emily J.
Abstract: Objectives: Servicewomen in Defence Forces the world over are constrained in their health service use by defence healthcare policy. These policies govern a woman's ability to choose who she receives maternity care from and where. The aim of this study was to compare Australian Defence Force (ADF) servicewomen and children's birth outcomes, health service use, and out-of-pocket costs to those of civilian women and children. Methods: Retrospective cohort study using linked administrative data for women giving birth between 1 July 2012 and 30 June 2018 in Queensland, Australia (n = 365, 138 births). Women serving in the ADF at the time of birth were identified as having their care funded by the Department of Defence (n = 395 births). Propensity score matching was used to identify a mixed public/private civilian sample of women to allow for comparison with servicewomen, controlling for baseline characteristics. Sensitivity analysis was also conducted using a sample of civilian women accessing only private maternity care. Findings: Nearly all servicewomen gave birth in the private setting (97.22%). They had significantly greater odds of having a caesarean section (OR 1.71, 95%CI 1.29−2.30) and epidural (OR 1.56, 95%CI 1.11−2.20), and significantly lower odds of having a non-instrumental vaginal birth (OR 0.57, 95%CI 0.43−0.75) compared to women in the matched public/private civilian sample. Compared to civilian children, children born to servicewomen had significantly higher out-of-pocket costs at birth (275.93 ± 355.82), in the first (214.98 ± 403.45) and second (127.75 ± 391.13) years of life, and overall up to two years of age (618.66 ± 779.67) despite similar health service use. Conclusions: ADF servicewomen have higher rates of obstetric intervention at birth and also pay significantly higher out-of-pocket costs for their children's health service utilisation up to 2-years of age. Given the high rates of obstetric intervention, greater exploration of servicewomen's maternity care experiences and preferences is warranted, as this may necessitate further reform to ADF maternity healthcare policy.